High Level Languages Implementation and Analysis of 3D Navier-Stokes Solvers (Advances in Applied Mathematics and Mechanics, 2021)
In this work we introduce PRIN-3D (PRoto-code for Internalflows modeled by Navier-Stokes equations in 3-Dimensions),a new high level algebraic language (Matlab$^®$) based code, by discussing some fundamental aspects regarding its basic solving kernel and by describing the design of an innovative advection scheme. The main focus was ondesigning a memory and computationally efficient code that, due to the typicalconciseness of the Matlab coding language, could allow for fast and effective implementation of new models or algorithms. Innovative numerical methods are discussed in the paper. The pressure equationis derived with a quasi-segregation technique leading to an iterative scheme obtained within the framework of a global preconditioning procedure. Different levels of parallelization are obtainable by exploiting specialpressure variable ordering patterns that lead to a block-structured Poisson-likematrix. Moreover, the new advection scheme has the potential of a controllable artificial diffusivity. Preliminary results are shown including a fully three-dimensional internallaminar flow evolving in a relatively complex geometry and a 3D methane-air flame simulated with the aid of libraries based on the Flamelet model.